Helping children develop a positive relationship with food : a practical guide for early years professionals - Cormack, Jo (Jessica Kingsley Publishers, 2018)
This simple, insightful resource explains how to help children develop a healthy relationship with food. Giving practical guidance on how to support lasting positive eating behaviours in children, it includes valuable information and advice about how to resolve issues including fussy eating, obesity, and special needs related feeding difficulties.